Pasja i antyk. Wawrzyńca Korwina (1465–1527) rozważania wielkanocne - Zawadzki, Robert K. (Collectanea Philologica, 2021)
The article is an attempt of interpretation of seven poems written by Wawrzyniec Korwin which were inserted in St. Bonaventura`s homilies and constitute forms of prayers to be said daily by Christians. The author analyses the artistic skill of the language used by the poet. His poems keep fascinating their readers because of their language, i.e. style as a system of remarkable pattern of linguistic elements and ancient metre.